(untitled) (Journal of Nobel Medical College, 2024)
Background: The correct estimation of gestational age is of great importance for managing pregnancy. Determining gestational age by the first-trimester scan is considered the gold standard, but classical calculation from the last menstrual period is also useful. Fetal biometry is widely used, but estimation from trans-cerebellar diameter can be very important, especially in low-income countries. Material and Methods: This was a prospective analytical study carried out in a Tertiary Care Centre from 21stMarch, 2023 to 20thMarch, 2024. Ethical clearance was taken from the Institutional Review Committee (Ref no:817/2023). Consecutive sampling was done to include 384 pregnant women in the third trimester of pregnancy. Variables collected were demographics, last menstrual period, first-trimester scan, and obstetrical ultrasound including fetal biometry and trans-cerebellar diameter. Analytical analysis for correlation and coefficient of determination was done. Results: A total of 384 third-trimester pregnancies were studied. A statistically significant correlation was seen between gestational age from trans cerebellar diameter and first-trimester scan (r=0.965, R2=93.12%,p<0.01) and with last menstrual period (r=0.941, R2=88.54%,p<0.01). The correlation of the first-trimester scan was better with trans-cerebellar diameter than with fetal biometry (r=0.938, R2=87.98%, p<0.01). The estimation of gestational age from trans-cerebellar diameter was better in the early weeks of the third trimester than in the later weeks. Conclusion: Trans-cerebellar diameter is an accurate parameter in the determination of gestational age in the third trimester. It is a better parameter to determine gestational age when compared to fetal biometry especially in the third trimester.